PENGARUH PENGGUNAAN GADGET DALAM KEGIATAN BELAJAR DAN MENGAJAR TERHADAP PEMBENTUKAN KARAKTER ANAK GENERASI Z - Anjani Syalsa Putri; Luthfi Indah Setyani; Nissa Aulia Rizkia; Arita Marini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
Gadgets are electronic media devices that have various functions and uses. Nowadays gadgets have become a part of life, even human lifestyle. Character as a basic value that builds a person's personality, is formed both due to heredity and environmental influences, which distinguishes it from other people, and is manifested in attitudes and behavior in everyday life. Generation Z has unique characteristics where the internet begins to develop and grow in line with the development of digital media. The purpose of this study was to determine the effect of using gadgets in teaching and learning activities on the formation of the character of Generation Z. The research method used was a literature study with a qualitative approach where the data source was taken from literature and documentation. The results of the analysis of this study reveal the use of gadgets in teaching and learning activities on the formation of the character of generation Z children, because the use of gadgets has impacts that must be considered.